Optimal Degree of Public Information Dissemination - Camille Cornand; Frank Heinemann (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Financial markets and macroeconomic environments are often characterized by positive externalities. In these environments, transparency may reduce expected welfare from an ex-ante point of view: public announcements serve as a focal point for higher-order beliefs and affect agents' behaviour more than justified by their informational contents. Some scholars conclude that it might be better to reduce the precision of public signals or entirely withhold information. This paper shows that public information should always be provided with maximum precision, but under certain conditions not to all agents. Restricting the degree of publicity is a better-suited instrument for preventing the negative welfare effects of public announcements than restrictions on their precision are.
urn:nbn:de:bvb:19-epub-13393-6
Keywords: C73; D82; F31; 330; Transparency; public information; private information; coordination; strategic complementarity